RANCANG BANGUN SISTEM INFORMASI PEMESANAN TRAVEL AR-RIYADH BERBASIS WEB MENGGUNAKAN MODEL USER CENTERED DESIGN - Jumaidi, Ahmad Mahbub; Dwanoko, Yoyok Seby; Purwanto, Hari Lugis (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2024)
One of the shortcomings of Ar-Riyadh travel is the lack of integration with sophisticated information technology. Companies face problems because the travel booking system still relies on manual processes. Customers make travel reservations via WhatsApp by contacting the travel operator, which is not yet computerized, thereby presenting the risk of loss and damage to data in stored archives. The aim of this research is to design a web-based Ar-Riyadh travel booking information system using a User Centered Design (UCD) approach. The research results show that this system has succeeded in making it easier for users to implement the travel booking information system and making the booking process easier.